Respuesta :

(h*h)(10) is the same as h(10)*h(10). Let's find the value of h(10) first. To do this, replace every x with 10 like so

h(x) = 6-x
h(10) = 6-10
h(10) = -4

So,
h(10)*h(10) = (-4)*(-4)
h(10)*h(10) = 16

The final answer is 16

Answer:  16

Step-by-step explanation:

The given function : [tex]h(x) = 6 - x[/tex]

We know that for any functions f(x) and g(x)

[tex]f*g (x)=f(x)\times g(x)[/tex]

Therefore , [tex]h*h (x)=h(x)\times h(x)[/tex]

[tex]h*h (x)=(6-x)(6-x)=(6-x)^2[/tex]

[tex]h*h (x)=(6)^2-2(6)(x)+x^2[/tex]    [ Using identity  [tex](a-b)^2=a^2+2ab+b^2[/tex] ]

[tex]h*h (x)=36-12(x)+x^2[/tex]

[tex]\Rightarrow\ h*h (x)=36-12(x)+x^2[/tex]

Now, at x= 10 , we get

[tex]h*h (10)=36-12(10)+(10)^2[/tex]

[tex]h*h (10)=36-120+100=36+100-120=136-120=16[/tex]

Hence, the value of (h*h)(10) = 16

ACCESS MORE